Frequency‐Selective Suppression of Essential Tremor via Transcutaneous Spinal Cord Stimulation - Pascual‐Valdunciel, Alejandro; Ibáñez, Jaime; Rocchi, Lorenzo; Song, Joy; Rothwell, John C.; Bhatia, Kailash P.; Farina, Dario; Latorre, Anna (Movement disorders, 2024)
Background Essential tremor (ET) is a common debilitating condition, yet current treatments often fail to provide satisfactory relief. Transcutaneous spinal cord electrical stimulation (tSCS) has emerged as a potential noninvasive neuromodulation technique capable of disrupting the oscillatory activity underlying tremors. Objective This study aimed to investigate the potential of tSCS to disrupt tremor in a frequency‐dependent manner in a cohort of patients with ET. Methods Eighteen patients with ET completed the study. The experiment consisted of 60‐s postural tremor recording, during tSCS at tremor frequency, at 1 Hz, at 21 Hz, no stimulation, and trapezius stimulation. Tremor frequency and amplitude were analyzed and compared across the conditions. Results We found tremor amplitude reduction at tremor frequency stimulation significant only during the second half of the stimulation. The same stimulation resulted in the highest number of responders. tSCS at 1 Hz showed a trend toward decreased tremor amplitude in the latter half of stimulation. tSCS at 21 Hz did not produce any significant alterations in tremor, whereas trapezius stimulation exacerbated it. Notably, during tremor frequency stimulation, a subgroup of responders exhibited consistent synchronization between tremor phase and delivered stimulation, indicating tremor entrainment. Conclusions Cervical tSCS holds promise for alleviating postural tremor in patients with ET when delivered at the subject's tremor frequency. The observed changes in tremor amplitude likely result from the modulation of spinal cord circuits by tSCS, which disrupts the oscillatory drive to muscles by affecting afferent pathways or spinal reflexes. However, the possibility of an interplay between spinal and supraspinal centers cannot be discounted. © 2024 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.